Investigating crucial elements of formula milk and the inadequacy of exclusive breastfeeding in Indonesia: A litarature review - Novitasari, Anis; Pramesti, Monica Ria; Adnani, Qorinah Estiningtyas Sakilah; Susiarno, Hadi (Science Midwifery, 2025)
Breast milk provides optimal nutrition for newborns, supporting their growth and development while meeting essential nutritional needs. Exclusive breastfeeding is crucial; however, many mothers face challenges that hinder their ability to breastfeed exclusively. Additionally, some parents believe that breast milk alone is insufficient, leading them to supplement with formula milk. Methods: This literature review analyzed studies from Google Scholar, Semantic Scholar, and Garuda, published between 2014 and 2024 in English or Indonesian. Only full-text quantitative or qualitative studies were included, assessed using the CASP tool, and data extraction followed a structured approach. The synthesis identified six predominant factors contributing to the failure of exclusive breastfeeding and the use of formula milk, which were further analyzed for interconnections. Results: The investigation produced 20 studies that highlighted the factors influencing formula milk use and the failure of exclusive breastfeeding in Indonesia. Key elements identified include understanding, spousal/family support, promotion of formula milk, maternal disposition, profession, and education. These factors were found to interact and exacerbate the challenges of exclusive breastfeeding. Conclusion: The review found that inadequate breastfeeding practices in Indonesia are primarily due to factors such as lack of knowledge, insufficient family support, the aggressive promotion of formula milk, maternal attitudes, work demands, and educational background. Addressing these issues through targeted interventions can improve breastfeeding rates and reduce the reliance on formula milk.